Applications of variable thermal features for the bioconvective flow of Jeffrey nanofluids due to stretching surface with mass suction effects: Cattaneo-Christov model - Khan, S. U.; Garayev, M.; Adnan; Ramesh, K.; El Meligy, M.; Abduvalieva, D.; Khan, M. I. (Applied mathematics and mechanics, 2025)
The thermal nanofluids have garnered widespread attention for their use in multiple thermal systems, including heating processes, sustainable energy, and nuclear reactions. Research on nanofluids has revealed that the thermal efficiencies of such materials are adversely affected by various thermal features. The purpose of the current work is to demonstrate the thermal analysis of Jeffrey nanofluids with the suspension of microorganisms in the presence of variable thermal sources. The variable effects of thermal conductivity, Brownian diffusivity, and motile density are utilized. The investigated model also reveals the contributions of radiation phenomena and chemical reactions. A porous, saturated, moving surface with a suction phenomenon promotes flow. The modeling of the problem is based on the implementation of the Cattaneo-Christov approach. The convective thermal constraints are used to promote the heat transfer features. A simplified form of the governing model is treated with the assistance of a shooting technique. The physical effects of different parameters for the problem are presented. The current problem justifies its applications in heat transfer, coating processes, heat exchangers, cooling systems in microelectronics, solar systems, chemical processes, etc.